(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
Ethylene glycol (EG) it is an odorless, colorless, sweet-tasting liquid used for automobile anti-freeze, and is moderately toxic if ingested the leaves of the Taraxacum officinale plant are used as an antioxidant and immune booster. It is found in many countries, including Iraq. The animals were divided into 5 groups, each containing 6 rabbits: the control group (untreated), the group of rabbits treated with ethylene glycol at a dose of 1% ethylene glycol in drinking water for 60 days, in addition to that, groups from three to five) were treated with 1% ethylene. Glycol in drinking water with injections of extracted extracts from Taraxacum officinale leaves (flavonoids, glycosides and alkaloids) at a single daily dose of 50 mg/kg body weight for two months. After the end of the experiment, blood was drawn into tubes devoid of anticoagulants to conduct some tests. Administration of ethylene glycol led to a significant decrease in the levels of measured antioxidants compared to the control group, except for SOD, while the groups treated with extracts isolated from the plant showed a decrease in MDA and a significant increase (P < 0.05) in Gpx, CAT, and GSH after treatment with Taraxacum extracts. officinale, while SOD increased significantly (P <0.05) compared to the ethylene glycol group. The pathological histopathological changes in the ethylene glycol group include the deposition of oxalates in the lumen of the renal tubules and atrophy of the glomerular tuft, which leads to the expansion of the Bowman’s space, necrosis of the epithelium of the renal tubules, congestion of blood cells and infiltration of inflammatory cells in the tissues of the kidneys, liver and heart, while treatment with extracts of Dandelion with ethylene glycol reduced necrosis in epithelial cells and decreased the number of inflammatory cells with less congestion in blood vessels in the tissues of the kidneys, liver and heart compared to the ethylene glycol group.